Isolated Hypoglossal Nerve Palsy Associated with Tuberculosis of the Atlantoaxial Joint: A Rare Case Report - Rocksy Fransisca V Situmeang; Nadia Gabriella; Koesbandono (Medicinus, 2026)
Background: Venous thromboembolism (VTE) is the third most common cardiovascular disorder worldwide. While lower-extremity deep vein thrombosis and pulmonary embolism are typical presentations, thrombosis in atypical sites remains challenging to recognize and diagnose.   Case Description: A 27-year-old female flight attendant with history inflammatory bowel disease (IBD), tuberculosis and combined oral contraceptive (COC) use presented with an acute abdominal pain. Initial contrast-enhanced CT revealed thrombosis of the left renal and ovarian veins. Laboratory tests showed elevated hs-CRP and D-dimer, with positive ANA but negative antiphospholipid antibodies. She was treated with intravenous heparin followed by oral rivaroxaban, though adherence was inconsistent due to episodes of heavy vaginal bleeding. Repeat CT imaging eight months later demonstrated resolution of the initial thrombi but revealed a new thrombus in the inferior vena cava extending into the right common iliac vein, accompanied by recurrent elevation of D-dimer.   This case illustrates the interplay of multiple risk factors for VTE, including IBD, prolonged immobility during long-haul travel, COC use, tuberculosis, and rifampicin therapy. These overlapping chronic and transient triggers likely contributed to recurrent thrombosis despite ongoing treatment.   Conclusions: Recurrent VTE in unusual venous sites can occur particularly in patients with multiple risk factors. Early recognition, appropriate imaging, and anticoagulant therapy adherence are essential to preventing progression and recurrence.